Method for passivating perovskite solar cell and perovskite solar cell
By using the passivator baiquanting with multiple reaction sites to interact with the surface of the perovskite layer, the defective density of defect states and the energy level gradient arrangement is improved, the shortcomings of the hole-free transport layer all-inorganic perovskite solar cells in photoelectric conversion efficiency and stability are solved, and an efficient and stable photoelectric conversion effect is achieved.
Patent Information
- Application Number
- CN202510047162.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-15
AI Technical Summary
The hole-free transport layer all-inorganic perovskite solar cells have shortcomings in photoelectric conversion efficiency and stability. This is mainly due to the large energy level barrier between the perovskite layer and the electrode layer, which leads to low carrier extraction and transmission efficiency, and the commonly used organic passivator binding capacity is weak, making it easy to introduce a transmission barrier.
The passivator baifoxil, which has multiple reaction sites, uses its unique conjugated structure to form a Lewis acid-base pair with halogen vacancy defects on the surface of the perovskite layer, reduces the defect state density, and allows the buckyfoxil to lie on the perovskite surface, avoiding the transmission barrier caused by vertical and tight packing of traditional passivators, and promoting the gradient energy level arrangement between the perovskite layer and the electrode layer.
It effectively improves the photoelectric conversion efficiency and stability of hole-free transport layer all-inorganic perovskite solar cells, reduces the preparation cost, simplifies the process, and promotes the commercialization process of perovskite solar cells.
Smart Images

Figure CN119836188A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solar cells, and in particular to a method for passivating a perovskite solar cell and a perovskite solar cell. Background Art
[0002] Perovskite solar cells have the advantages of high photoelectric absorption characteristics, high carrier mobility, adjustable optical band gap, and simple preparation methods, and have become one of the research hotspots of photovoltaic cells. Their energy conversion efficiency has been rapidly improved. Due to the presence of volatile organic cations in organic-inorganic hybrid perovskite solar cells, their thermal stability is subject to certain restrictions.
[0003] CsPbI can be prepared by replacing the organic cation at the A position with an inorganic cesium ion. X Br 3-X (X≤3) All-inorganic perovskite solar cells, which have excellent optoelectronic properties and thermal stability. The band gap of all-inorganic perovskite solar cells can be continuously adjusted between 1.73eV (CsPbI3) and 2.30eV (CsPbBr3), which can be used as a single junction cell or as the top cell of a tandem cell. In addition, the hole transport layer is relatively expensive, which greatly limits the commercialization of perovskite solar cells. All-inorganic perovskite solar cells without hole transport layers can greatly improve their stability and significantly reduce their preparation costs.
[0004] At present, all-inorganic perovskite solar cells without hole transport layers have made great progress, but their photoelectric conversion efficiency still lags behind that of organic-inorganic hybrid perovskite solar cells. The main reasons are as follows.
[0005] 1. When the electrode layer is in direct contact with the perovskite layer, higher requirements are placed on the crystallization quality and surface morphology of the perovskite film. 2. There is a large energy level barrier between the valence band energy level of the perovskite and the work function of the carbon electrode, resulting in low hole extraction and transmission efficiency, and at the same time, it is unable to effectively inhibit the transfer of electrons to the carbon electrode, thus causing serious charge recombination. 3. Currently commonly used organic passivation molecules can usually only bind to a single active site on the perovskite surface, have weak binding ability, and tend to stack vertically and tightly on the upper surface of the perovskite, introducing a transmission barrier at the perovskite / carbon electrode interface, affecting charge extraction.
[0006] Therefore, how to passivate the defects of the perovskite layer, promote the gradient distribution of the interface energy level, improve the crystallization quality of the perovskite film, reduce the transmission barrier, and achieve excellent interface contact has become an urgent problem to be solved for all-inorganic perovskite solar cells without a hole transport layer. Summary of the invention
[0007] In order to passivate the defects of the perovskite film, reduce its defect state density, and at the same time construct a gradient energy level arrangement to reduce the transmission barrier, the present invention provides a method for passivating a perovskite solar cell and a perovskite solar cell. The present invention provides a passivator with multiple binding sites, which can passivate multiple defects at the same time and effectively reduce the defect state density of the perovskite solar cell. In addition, while passivating the defects, the passivator can lie flat on the surface of the perovskite layer to avoid the transmission barrier formed after the traditional passivator is vertically and tightly stacked. It can promote the energy level gradient arrangement between the perovskite layer and the electrode layer, reduce the energy level barrier, and make the extraction and transfer of carriers more efficient. Therefore, the present invention can effectively improve the photoelectric conversion efficiency and stability of the all-inorganic perovskite solar cell without a hole transport layer, and the preparation process is simple and low cost, which is conducive to promoting the large-scale application and commercialization progress of perovskites, and has broad application prospects.
[0008] A perovskite solar cell provided by the present invention comprises the following structure: conductive substrate\electron transport layer\perovskite layer\flat passivation layer\electrode layer.
[0009] The flat passivation layer is composed of a passivation agent, thiophanate-methyl (TPN), which has multiple reaction sites and a unique molecular structure. The thiophanate-methyl molecular structure is a conjugated structure with two symmetrically distributed cyano groups and four symmetrically distributed chlorine atoms, which can simultaneously rivet two uncoordinated divalent lead ions (Pb 2+ ) forms a Lewis acid-base pair and simultaneously passivates the halogen vacancy defects on the surface of the perovskite, effectively reducing the generation of non-radiative recombination. Multiple reactive active sites enable the rigid conjugated structure of chlorothalonil to lie flat on the surface of the perovskite, avoiding the formation of a transmission barrier caused by the vertical and tight stacking of the single-point passivator, promoting the gradient energy level arrangement between the perovskite layer and the carbon electrode, and enhancing the carrier separation and hole extraction capabilities. In addition, when chlorothalonil lies flat on the surface of the perovskite, the benzene ring in its molecular structure is exposed, increasing the hydrophobic properties of the perovskite, thereby improving the humidity stability of the perovskite solar cell.
[0010] The present invention provides a method for passivating a perovskite solar cell, and its technical solution comprises the following steps:
[0011] (1) After cleaning and drying the conductive substrate, an electron transport layer is assembled on the conductive surface;
[0012] (2) preparing a perovskite precursor according to a certain concentration, dissolving it in solvent A, and stirring until the solution becomes clear to obtain a perovskite precursor solution; dissolving an appropriate amount of thiophanate-methyl in solvent B to prepare a thiophanate-methyl solution of a certain concentration;
[0013] (3) Plasma treating the substrate on which the electron transport layer has been assembled for 5-35 minutes; then transferring it to a spin coater under an inert gas atmosphere, dripping a certain amount of perovskite precursor solution on the upper surface of the electron transport layer, standing it for 30-300 seconds, and then spin coating it at a speed of 400-10000 rpm for 8-130 seconds. After the spin coating is completed, placing the substrate with the perovskite wet film in an inert gas atmosphere for 15-50 minutes to allow the solvent to evaporate slowly, control the perovskite nucleation rate and crystallization quality, and then transferring it to an air atmosphere with a relative humidity of 20% RH-60% RH, placing it on a hot stage at 100-200° C. for annealing for 5-30 minutes to prepare a perovskite layer;
[0014] (4) placing the substrate with the perovskite layer cooled to room temperature on a spin coater, dripping a certain amount of thiophanate-methyl solution on the upper surface thereof, standing for 30-180 seconds, and then rotating at a speed of 500-3000 rpm for 5-30 seconds. After the spin coating is completed, the substrate is transferred to a hot plate at 70-120° C. and annealed for 3-15 minutes, thereby preparing a flat passivation layer;
[0015] (5) Assemble the electrodes onto the above substrate.
[0016] The blank control group is a perovskite solar cell without a flat passivation layer. The preparation method thereof is the same as that of the control group except that step (4) is omitted.
[0017] The preferred conductive substrate is any one of FTO and ITO;
[0018] The preferred electron transport layer is any one of PCBM, TiO2, ZnO-ZnS, SnO2, and ZnO;
[0019] The preferred solvent A is any one of DMSO, DMF, 1-methyl-2-pyrrolidone (NMP) or a mixture of any of them in any ratio;
[0020] The preferred solvent B is any one of isopropanol, chlorobenzene, ethyl acetate, and ether, or a mixture of any of them in any ratio;
[0021] The preferred inert gas is any one of nitrogen and argon;
[0022] The relative humidity of the preferred air atmosphere is 20% RH-60% RH;
[0023] The preferred standing time of the perovskite wet film in an inert gas atmosphere is 15-50 minutes;
[0024] The preferred volume of the perovskite precursor to be added is 30-250 μL;
[0025] The preferred concentration of the perovskite precursor is 0.5M-1.8M, and the prepared perovskite layer is an all-inorganic perovskite CsPbI X Br 3-X (X≤3);
[0026] The preferred concentration of thiophanate-methyl solution is 0.5 mg / mL-10 mg / mL;
[0027] The preferred volume of the thiophanate-methyl solution added dropwise is 10-200 μL;
[0028] The preferred electrode material is any one of gold, silver, aluminum, copper and carbon.
[0029] The flat passivation layer is produced by passivation with chlorothalonil solution. The conjugated chlorothalonil has two symmetrically distributed cyano groups and four symmetrically distributed chlorine atoms, which can simultaneously rivet two uncoordinated Pb 2+ The Lewis acid-base pair is formed and the halogen vacancy defects on the surface of the perovskite are passivated at the same time, effectively reducing the generation of non-radiative recombination. Multiple reactive active sites enable the rigid conjugated structure of chlorothalonil to lie flat on the surface of the perovskite, avoiding the transmission barrier formed by the vertical and tight stacking of traditional passivators. In addition, when chlorothalonil lies flat on the surface of the perovskite, the benzene ring in the molecular structure is exposed, promoting the gradient energy level arrangement between the perovskite layer and the carbon electrode, enhancing the hole extraction ability and improving the hydrophobic properties of the perovskite.
[0030] The beneficial effect of the present invention is that after passivation modification with thiophanate-methyl, the conjugated thiophanate-methyl has two symmetrically distributed cyano groups and four symmetrically distributed chlorine atoms, which can simultaneously rivet two uncoordinated Pb 2+ It forms a Lewis acid-base pair and simultaneously passivates the halogen vacancy defects on the surface of the perovskite, doubly passivates the defects of the perovskite layer, thereby reducing the defect state density and reducing non-radiative recombination. On the other hand, there are multiple reaction sites between chlorothalonil and perovskite, which can make the rigid conjugated structure of chlorothalonil lie flat on the surface of the perovskite, avoiding the transmission barrier formed by the vertical and tight stacking of traditional passivators, and enabling rapid carrier transfer. In addition, when chlorothalonil lies flat on the surface of the perovskite, the hydrophobic benzene ring in the molecular structure is exposed, which promotes the gradient energy level arrangement between the perovskite layer and the carbon electrode, making the transfer and extraction of holes more efficient, thereby improving the photoelectric conversion efficiency and stability of perovskite solar cells. The passivation method has a simple process and is easy to operate. It can effectively improve the photoelectric conversion efficiency and stability of perovskite solar cells, promote the commercialization process of perovskite solar cells, and has great market value and broad application prospects.
[0031] The present invention is further described below in conjunction with the accompanying drawings.
[0032] Figure 1It is a schematic structural diagram of a perovskite solar cell prepared according to Example 1 of the present invention.
[0033] 1-substrate, 2-electron transport layer, 3-perovskite layer, 4-flat passivation layer, 5-electrode layer.
[0034] Figure 2 This is a surface morphology of a perovskite solar cell prepared according to Example 1.
[0035] Figure 3 It is a schematic diagram of the energy level gradient arrangement of the perovskite solar cell prepared according to Example 1.
[0036] Figure 4 It is a JV curve diagram of the control group perovskite solar cell prepared according to Example 1 and the perovskite solar cell with a flat passivation layer.
[0037] Figure 5 This is a schematic diagram of the molecular structure of thiophanate-methyl. DETAILED DESCRIPTION
[0038] The present invention is further described below by way of examples.
[0039] Embodiment 1:
[0040] (1) The conductive substrate ITO was cleaned with deionized water, ethanol, acetone, and isopropanol in turn by ultrasonic treatment for 15 min each and then dried with nitrogen gas; then, the SnO2 nanoparticle precursor was mixed with water in a ratio of 1:3 and spin-coated onto the ITO surface at a speed of 4000 rpm for 30 seconds; then, the coated ITO substrate was placed on a hot plate at 170°C and heated for 1 hour to prepare a SnO2 electron transport layer.
[0041] (2) According to the stoichiometric ratio, quantitative DMAI, CsI, PbI2 and PbBr2 were weighed in sequence, dissolved in a mixed solvent of DMSO and DMF with a volume ratio of 3:2, placed on a hot plate at 60°C and stirred until the solution was clear, thereby preparing a perovskite precursor solution; chlorothalonil was dissolved in a chlorobenzene solution to prepare a chlorothalonil solution with a concentration of 4 mg / mL;
[0042] (3) The substrate with the SnO2 electron transport layer was treated with ozone for 15 minutes; then it was transferred to a spin coater in a nitrogen glove box, 55 μL of the perovskite precursor solution was dripped onto its upper surface, and after standing for 30 seconds, the substrate was spin-coated at 2600 rpm for 60 seconds; after the spin coating was completed, the substrate with the perovskite wet film was allowed to stand in the nitrogen glove box for 30 minutes, and then it was quickly transferred to an air atmosphere with a relative humidity of 50% RH and placed on a hot plate at 170°C for annealing for 10 minutes to prepare the perovskite layer;
[0043] (4) placing the substrate with the perovskite layer cooled to room temperature on a spin coater, dripping 60 μL of chlorothalonil solution on the upper surface and letting it stand for 2 min, then spinning it at 4000 rpm for 20 seconds. After the spin coating, transferring it to a hot plate at 90° C. for annealing for 2 minutes to prepare a flat passivation layer;
[0044] (5) The carbon slurry was scraped onto the flat passivation layer and annealed on a hot plate at 120°C for 10 min to prepare a carbon electrode layer.
[0045] The surface microstructure of the perovskite solar cell prepared in Example 1 and the schematic diagram of the gradient energy level are shown in Figures 1 and 2. Figure 2 , Figure 3 As shown, it can be clearly seen that the perovskite surface with a flat passivation layer is smooth; Figure 4 It can be clearly seen that the photoelectric conversion efficiency, open circuit voltage and fill factor of perovskite solar cells containing a flat passivation layer are significantly improved.
[0046] Embodiment 2:
[0047] (1) The conductive substrate FTO was cleaned by ultrasonic cleaning with deionized water, ethanol, acetone, and isopropanol for 35 minutes each, and then dried in an oven; a dense TiO2 electron transport layer was prepared on the conductive surface;
[0048] (2) According to the stoichiometric ratio, quantitative DMAI, CsI, PbI2 and PbBr2 were weighed in sequence, dissolved in DMSO solvent, placed on a hot plate at 50°C and stirred until the solution was clear, to prepare a 1.8 M perovskite precursor solution; chlorothalonil was dissolved in ether solution to prepare a chlorothalonil solution with a concentration of 10 mg / mL;
[0049] (3) The substrate with the TiO2 electron transport layer was treated with ozone for 35 minutes; then it was transferred to a spin coater in a nitrogen glove box, 250 μL of the perovskite precursor solution was dripped onto its upper surface, and after standing for 300 seconds, it was spin-coated at a speed of 10,000 rpm for 8 seconds; after the spin coating was completed, the substrate with the perovskite wet film was allowed to stand in the nitrogen glove box for 50 minutes, and then it was quickly transferred to an air atmosphere with a relative humidity of 60% RH and placed on a hot plate at 200°C for annealing for 15 minutes to prepare the perovskite layer;
[0050] (4) placing the substrate with the perovskite layer cooled to room temperature on a spin coater, dripping 200 μL of chlorothalonil solution on the upper surface, letting it stand for 180 seconds and then spinning it at 3000 rpm for 5 seconds. After the spin coating is completed, it is transferred to a hot plate at 120° C. and annealed for 3 minutes, thereby preparing a flat passivation layer;
[0051] (5) Depositing metallic gold onto the perovskite layer by vapor deposition to prepare a gold electrode layer.
[0052] Embodiment 3:
[0053] (1) The conductive substrate ITO was cleaned by ultrasonic cleaning with deionized water, ethanol, acetone, and isopropanol for 5 minutes each, and then dried with an infrared lamp; a PCBM electron transport layer was prepared on the conductive surface;
[0054] (2) According to the stoichiometric ratio, a certain amount of CsI, PbBr2, and PbI2 were weighed in sequence, dissolved in a solvent of DMSO:NMP=9:1, placed on a hot plate at 70°C and stirred until the solution was clear, to prepare a 0.5 M perovskite precursor solution; chlorothalonil was dissolved in an isopropanol solution to prepare a 0.5 mg / mL chlorothalonil solution;
[0055] (3) The substrate with the PCBM electron transport layer was treated with ozone for 5 minutes; then it was transferred to a spin coater in a nitrogen glove box, 30 μL of the perovskite precursor solution was dripped on its upper surface, and after standing for 30 seconds, it was spin-coated at 400 rpm for 8 seconds; after the spin coating was completed, the substrate with the perovskite wet film was allowed to stand in the nitrogen glove box for 15 minutes, and then it was quickly transferred to an air atmosphere with a relative humidity of 20% RH and placed on a hot stage at 100°C for annealing for 30 minutes to prepare the perovskite layer;
[0056] (4) placing the substrate with the perovskite layer cooled to room temperature on a spin coater, dropping 10 μL of chlorothalonil solution on the upper surface, letting it stand for 30 seconds and then rotating it at a speed of 500 rpm for 30 seconds. After the spin coating is completed, it is transferred to a hot plate at 70° C. and annealed for 15 minutes, thereby preparing a flat passivation layer;
[0057] (5) Depositing metallic silver onto the perovskite layer by vapor deposition to prepare a silver electrode layer.
[0058] Embodiment 4:
[0059] (1) The conductive substrate FTO was cleaned by ultrasonic cleaning with deionized water, ethanol, acetone, and isopropanol for 20 minutes in sequence and then completely dried; a dense ZnO electron transport layer was prepared on the conductive surface;
[0060] (2) According to the stoichiometric ratio, a certain amount of CsI, PbBr2, and PbI2 were weighed in sequence, dissolved in a solvent of DMSO:DMF=5:5, placed on a hot plate at 70°C and stirred until the solution was clear, to prepare a 1.2 M perovskite precursor solution; chlorothalonil was dissolved in an ethyl acetate solution to prepare a 6 mg / ml chlorothalonil solution;
[0061] (3) The substrate with the ZnO electron transport layer was treated with ozone for 15 minutes; then it was transferred to a spin coater in an argon glove box, 100 μL of the perovskite precursor solution was dripped onto its upper surface, and after standing for 150 seconds, it was spin-coated at a speed of 5000 rpm for 60 seconds; after the spin coating was completed, the substrate with the perovskite wet film was allowed to stand in a nitrogen glove box for 25 minutes, and then it was quickly transferred to an air atmosphere with a relative humidity of 40% RH and placed on a hot stage for annealing at 150°C for 20 minutes to prepare the perovskite layer;
[0062] (4) placing the substrate with the perovskite layer cooled to room temperature on a spin coater, dropping 100 μL of chlorothalonil solution on the upper surface, letting it stand for 90 seconds and then rotating it at a speed of 1500 rpm for 15 seconds. After the spin coating is completed, it is transferred to a hot plate at 90° C. and annealed for 9 minutes, thereby preparing a flat passivation layer;
[0063] (5) Metallic copper is deposited onto the perovskite layer by vapor deposition to prepare a copper electrode layer.
[0064] The embodiments are only used to illustrate the present invention and do not limit the scope of the present invention. The specific implementation methods described above further describe the purpose, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not used to limit the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for passivating a perovskite solar cell, the technical solution of which comprises the following steps: (1) After cleaning and drying the conductive substrate, an electron transport layer is assembled on the conductive surface; (2) preparing a perovskite precursor according to a certain concentration, dissolving it in solvent A, and stirring until the solution becomes clear to obtain a perovskite precursor solution; dissolving an appropriate amount of thiophanate-methyl in solvent B to prepare a thiophanate-methyl solution of a certain concentration; (3) Plasma treating the substrate on which the electron transport layer has been assembled for 5-35 minutes; then transferring it to a spin coater under an inert gas atmosphere, dripping a certain amount of perovskite precursor solution on the upper surface of the electron transport layer, letting it stand for 30-300 seconds, and then spin coating it at a speed of 400-10000 rpm for 8-130 seconds. After the spin coating is completed, placing the substrate with the perovskite wet film in an inert gas atmosphere for 15-50 minutes to allow the solvent to evaporate slowly, control the perovskite nucleation rate and crystallization quality, and then transferring it to an air atmosphere with a relative humidity of 20% RH-60% RH, and annealing it on a hot stage at 100-200° C. for 5-30 minutes to prepare a perovskite layer; (4) placing the substrate with the perovskite layer cooled to room temperature on a spin coater, dripping a certain amount of thiophanate-methyl solution on the upper surface thereof, standing for 30-180 seconds, and then rotating at a speed of 500-3000 rpm for 5-30 seconds. After the spin coating is completed, the substrate is transferred to a hot plate at 70-120° C. and annealed for 3-15 minutes, thereby preparing a flat passivation layer; (5) Assemble the electrodes onto the above substrate.
2. The method according to claim 1, characterized in that: The electron transport layer is any one of PCBM, TiO2, ZnO-ZnS, SnO2 and ZnO.
3. The method according to claim 1, characterized in that: The solvent A is any one of DMSO, 1-methyl-2-pyrrolidone, and DMF, or a mixture of any of them in any ratio.
4. The method according to claim 1, characterized in that: The solvent B is any one of isopropanol, chlorobenzene, ethyl acetate and ether or a mixture of any of them in any ratio.
5. The method according to claim 1, characterized in that: The molar concentration of the perovskite precursor is 0.5M-1.8M, and the prepared perovskite layer is an all-inorganic perovskite CsPbI X Br 3-X (X≤3).
6. The method according to claim 1, characterized in that: The concentration of the thiophanate-methyl solution is 0.5 mg / mL-10 mg / mL.
7. The method according to claim 1, characterized in that: The volume of the dropwise added thiophanate-methyl solution is 10-200 μL.
8. The method according to claim 1, characterized in that: The perovskite wet film is placed in an inert gas atmosphere for a standing time of 15-50 minutes.
9. The method according to claim 1, characterized in that: The relative humidity of the air atmosphere is 20%RH-60%RH.
Citation Information
Cited By
Perovskite solar cell based on carbon electrode and all-air preparation method thereof
CN121152537A